Echoes of Evil: Haunted Houses and Lingering Terrors in "The Amityville Horror" and "The Conjuring" - Seltnerajch, Julia (Zagadnienia Rodzajów Literackich, 2025)
Bruce F. Kawin defines horror by its recurring motifs and its primary goal: to frighten and unsettle the audience (4). Beyond its entertainment value, horror functions within a dynamic semiotic space, where spatial structures encode tensions between order and chaos. Within Lotman’s semiosphere, the haunted house serves as a centre-periphery battlefield, where the supernatural disrupts domestic stability, shifting the house from a structured centre into a peripheral, liminal space. This article examines the haunted residence trope in Andrew Douglas’ The Amityville Horror and James Wan’s The Conjuring, analysing how spatial boundaries define the interplay between demonic forces and human attempts to reclaim domestic space. Both films, despite distinct narratives, construct the haunted house as a contested space, where supernatural peripheries threaten to consume the centre. In The Amityville Horror, the house undergoes total peripheralization, rendering it uninhabitable and reinforcing the idea of an irredeemable periphery. In contrast, The Conjuring presents a liminal haunting, where the periphery can be exorcised, restoring the house’s central function. The periphery — comprising of basements, attics, gardens, and liminal spaces — functions as an intermediary zone, where supernatural incursions blur the boundary between the mundane and the horrific. By mapping the spatial dynamics of horror, this article explores how haunted houses embody cultural anxieties about the fragility of domestic order, demonstrating how the centre-periphery dichotomy structures horror’s evolving semiosphere.